A Study Into Certain Aspects Of Drug Education Programmes In Malaysian Schools. - Choo, Dr. Peter, Piang Fong; Ismail, Profesor Madya (Dr.) Maznah; Navaratnam, Profesor Madya (Dr.) V.; Md. Jewa, Profesor Madya (Dr.) Tunku Ismail; Ahmad, Azizah; Abdul Karim, Abdul Khalid (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1983)
Studies conducted by the National Drug Research Centre have shown that 11.6% of 16,166 school children surveyed have had some experience with non-medical use of drugs and that a trend towards multiple drug use was becoming evident. Epidemiological studies conducted by the Centre also showed that 30% of the addicts started using drugs before reaching the. age of 19 (Navaratnam &Spencer, 1981).